2021
DOI: 10.1136/bmjgh-2021-007433
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic minority status as social determinant for COVID-19 infection, hospitalisation, severity, ICU admission and deaths in the early phase of the pandemic: a meta-analysis

Abstract: IntroductionEarly literature on the COVID-19 pandemic indicated striking ethnic inequalities in SARS-CoV-2-related outcomes. This systematic review and meta-analysis aimed to describe the presence and magnitude of associations between ethnic groups and COVID-19-related outcomes.MethodsPubMed and Embase were searched from December 2019 through September 2020. Studies reporting extractable data (ie, crude numbers, and unadjusted or adjusted risk/ORs) by ethnic group on any of the five studied outcomes: confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
69
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 26 publications
8
69
0
1
Order By: Relevance
“…Furthermore, a pooled analysis of ethnic vulnerability due to the first wave pandemic lockdown revealed that the hospitalization rate was higher for ethnic minorities in the US and Europe. Hispanics, Asians, and Black African Americans were 2.08, 1.59, and 1.53 times more likely to be hospitalized than Whites, respectively [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a pooled analysis of ethnic vulnerability due to the first wave pandemic lockdown revealed that the hospitalization rate was higher for ethnic minorities in the US and Europe. Hispanics, Asians, and Black African Americans were 2.08, 1.59, and 1.53 times more likely to be hospitalized than Whites, respectively [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disproportionate burden of morbidity and mortality from COVID in racial and ethnic minorities has been well-documented and should elicit further investigation [ 6 , 7 , 8 , 9 , 27 , 29 , 30 , 43 , 48 ]. According to the New York State Department of Health, approximately 34% and 28% of COVID fatalities are Hispanic or Black, despite comprising 29% and 22% of the population, respectively [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent European registry analysis (On COVID) of 2634 patients with cancer diagnosed with COVID, also showed that mortality has improved in subsequent waves of the pandemic, which is reassuring and temporal trends in COVID outcomes should continue to be evaluated [26]. The disproportionate burden of morbidity and mortality from COVID in racial and ethnic minorities has been well-documented and should elicit further investigation [6][7][8][9]27,29,30,43,48]. According to the New York State Department of Health, approximately 34% and 28% of COVID fatalities are Hispanic or Black, despite comprising 29% and 22% of the population, respectively [49].…”
Section: Discussionmentioning
confidence: 99%
“…A pooled analysis of ethnic vulnerability due to the first wave pandemic lockdown revealed that the hospitalization rate was higher for ethnic minorities in the US and Europe. Hispanics, Asians and Black African-Americans were 2.08, 1.59 and 1.53 times more likely to be hospitalized than Whites [34].…”
Section: Introductionmentioning
confidence: 89%